2020
DOI: 10.1002/chem.202000218
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Racemization of Tertiary P‐Chiral Ferrocenyl Phosphines

Abstract: Te rtiary phosphinesa re generally knownt o Scheme1.P-Stereogenic ferrocenyl phosphine boranes 1a-c. [a] Dr.Supporting information and the ORCID identification number(s) for the author(s) of this articlecan be found under: https://doi.All given values are in kJ mol À1 .[a] See the Supporting Information for details. [b] DFT with ORCA: [37,38] PWPB95 [39] /def2-QZVP [40,41] . Figure 3. Calculated [37][38][39][40][41] structure of 2a.U pon protonation the internal dihedral angle (PCCC) is significantly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Thermal inversion at phosphorus under catalytic conditions was excluded, since previously reported inversion barriers for the monomeric complexes 3a-c-ML-Ru indicated an estimated half-life of several days at 85°C. [68] The enantioselectivity was only marginally better at low conversions, and lowering the temperature in general did not improve the enantioselection, but led to deficient conversions even for the monomeric precursors indicating slow deactivation over time. [74]…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal inversion at phosphorus under catalytic conditions was excluded, since previously reported inversion barriers for the monomeric complexes 3a-c-ML-Ru indicated an estimated half-life of several days at 85°C. [68] The enantioselectivity was only marginally better at low conversions, and lowering the temperature in general did not improve the enantioselection, but led to deficient conversions even for the monomeric precursors indicating slow deactivation over time. [74]…”
Section: Entrymentioning
confidence: 99%
“…Recently, we prepared three P-stereogenic ferrocenyl phosphine boranes 2a-c-ML with a 4-methoxyphenyl substituent in the 1′-position of the ferrocenyl group (Scheme 1). [67,68] In these monomeric (non-dendritic) ligands (ML) the 4-methoxyphenyl substituent serves to mimic the phenol linker which is needed in immobilization reactions. The P-stereogenic ferrocenyl phosphine boranes 2a-c-ML were synthesized with excellent enantiopurity (> 95 % ee in all cases) and subsequent borane-deprotection by heating in diethylamine, followed by reaction with [{Ru(p-cymene)Cl 2 } 2 ], yielded the monomeric ruthenium complexes 3a-c-ML-Ru.…”
Section: Synthesis Of P-stereogenic Ferrocenyl Phosphinesmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Constructing multi-ferrocene systems is usually motivated by the redox properties of the individual ferrocene moieties which, when assembled, can add up to more than the mere sum of its parts. 16,17 Motivated by the prominence of C 3 -symmetry in modern-day ligand design and the potential to exploit the use of three ferrocenyl groups for redox-switchable catalysis (RSC), we have built upon our previous works on ferrocenylphosphanes [18][19][20][21][22][23][24][25][26] and their applications in RSC [27][28][29] and reported a new family of tris-phosphanes (1a-d, Scheme 1) based on a redox-active, C 3 -symmetric tris(ferrocenyl)arene backbone. By incorporating an electronwithdrawing (b and c) or a tris-benzylic arene core (d), the electrochemical response as well as more subtle inuences on the coordination behaviour of the corresponding phosphanes become adjustable.…”
Section: Introductionmentioning
confidence: 99%
“…A few very recent reports indicate that such reactions, for example acid-catalysed and SET-facilitated processes, do occur under certain conditions. 7 Relatively recently, we have shown that halophosphonium salts [R 3 P-X] + X − (XPS, X = Cl, Br) which are the key dynamic resolution intermediates in P -asymmetric Appel reaction 8 , undergo rapid epimerization characterized by low activation barriers ca. 10–12 kcal mol −1 .…”
mentioning
confidence: 99%